Cross-talking between baculoviruses and host insects towards a successful infection. (14th January 2019) - Wang, Manli; Hu, Zhihong
Abstract : Baculoviridae is a family of large DNA viruses that infect insects. They have been extensively used as safe and efficient biological agents for the control of insect pests. As a result of coevolution with their hosts, baculoviruses developed unique life cycles characterized by the production of two distinctive virion phenotypes, occlusion-derived virus and budded virus, which are responsible for mediating primary infection in insect midgut epithelia and spreading systemic infection within infected insects, respectively. In this article, advances associated with virus–host interactions during the baculovirus life cycle are reviewed. We mainly focus on how baculoviruses exploit versatile strategies to overcome diverse host barriers and establish successful infections. For example, in the midgut, baculoviruses encode enzymes to degrade peritrophic membranes and use a series of per os infectivity factors to initiate primary infection. A viral fibroblast growth factor is expressed to attract tracheoblasts that spread the virus for systemic infection. Baculoviruses use different strategies to suppress host defence systems, including apoptosis, melanization and RNA interference. Additionally, baculoviruses can manipulate host physiology and induce 'tree-top disease' for optimal virus replication and dispersal. These advances in our understanding of baculoviruses will greatly inform the development of more effective baculoviral pesticides. This article is part of the theme issue 'Biotic signalling sheds light on smart pest management'.